Aquagenic palmoplantar keratoderma and cystic fibrosis. - Mazzotta, F. (European Journal of Pediatric Dermatology, 2023)
Cystic fibrosis (CF) is the most frequent and serious of the rare inherited diseases. This is why scientific research is oriented towards the search for increasingly precocious and side-effect-free diagnostic methods. A possible dermatological marker of CF is the so-called aquagenic keratoderma (AK), which is a characteristic wrinkled appearance of the hands and sometimes of the feet that appears a few minutes after contact with water. A case of AK in a 4-year-old boy whose father and sister were healthy cariers of the F508 mutation stimulated discussion of genotype/phenotype relationships in AK and of the latest non-invasive methods for early diagnosis of CF.